CLASSROOM ACTIVITIES BASED ON MULTIPLE INTELLIGENCE THEORY IN ENGLISH LANGUAGE TEACHING 2013 CURRICULUM FOR SEVENTH GRADE - Dea Feradepi; Dedi Sofyan; Kasmaini Kasmaini (Universitas Galuh, 2019)
The purpose of this study was to analyze whether schools had implemented the 2013 curriculum system such as the Bengkulu City 11 Junior High School in the learning process in classroom activities using multiple intelligence theories. This research was designed as a descriptive qualitative method. The population and sample of this study were English language teachers at SMPN 11 Bengkulu Cityin seventh grade. Data was collected using observations checklist and video recorder that were used to assist researchers in analyzing forms of observation checklist. The results of the study showed several continuations implemented from the three teachers, namely 100% linguistics, 66.7% visual and 66.7% body intelligence. Linguistic intelligence was the dominant one. from three teachers who taught in seventh grade with the same material namely descriptive text, the results showed, teacher A asked for three linguistic, visual and body intelligences, teacher B applied one linguistic intelligence and teacher C used three linguistic, visual, and body intelligences. The results show from the three teachers implemented linguistic intelligence more often in teaching English. Because in English lesson oriented to linguistic. Keywords:multiple intelligence, English teacher